Analisis Kepuasaan Konsumen Pada Produk Mobil Di PT. Hasjrat Abadi Cabang Manado (Dealer Toyota) - Wahongan, Stefanly; Tumbel, Tinneke M.; Walangitan, Olivia F. C. (Sam Ratulangi University, 2019)
The purpose of this study was to determine customer satisfaction in the products of PT. Hasjrat Abadi branch Manado. This study uses interview data collection techniques and observations with qualitative descriptive data analysis techniques. The focus of this study is customer satisfaction with the services of PT. Hasjrat Abadi branch of Manado measured from several aspects: 1) Consumer satisfaction in the process of car purchase administration, 2) Consumer satisfaction with the quality of products purchased, 3) Consumer satisfaction with response from officers regarding Consumer complaints regarding car disturbances or technical problems, 4) Customer satisfaction with handling problems or technical problems of the car. Results of the study indicate that administrative procedures at the time of product purchase are still lacking. Likewise with customer satisfaction with the quality of the vehicle during use. Many complained that some items from the car products purchased were still lacking. Or not according to what was promoted. Furthermore, some customers say that the company is less alert and responsive to complaints submitted by customers on technical matters of The the products purchased. The latter is also carried out that repair services for damage experienced in purchased car products are still not satisfactory. In the sense that the improvements carried out have not been maximized.